Special Issue Editorial - Marcelle Burns (Legal Education Review, 2019)
Extract: Over the past thirty years the need for legal professionals to become culturally competent have been repeated in numerous reports and inquiries. The Indigenous Cultural Competency for Legal Academics Program (ICCLAP) was designed to address this apparent gap in legal education. Led by a team of Indigenous legal academics - the project’s core aims were to consult with Aboriginal and Torres Strait Islander legal services, key stakeholders and legal academics to conceptualise what ICC means in the context of legal education; identify knowledge gaps, professional development needs, and guiding principles for embedding ICC; develop workshops and resources for legal academics; and foster a community of practice to support the embedding of ICC in law curricula.